Centromere size scales with genome size across Eukaryotes - Plačková, Klára; Bureš, Petr; Zedek, František (Scientific reports, 2021)
Previous studies on grass species suggested that the total centromere size (sum of all centromere sizes in a cell) may be determined by the genome size, possibly because stable scaling is important for proper cell division. However, it is unclear whether this relationship is universal. Here we analyze the total centromere size using the CenH3-immunofluorescence area as a proxy in 130 taxa including plants, animals, fungi, and protists. We verified the reliability of our methodological approach by comparing our measurements with available ChIP-seq-based measurements of the size of CenH3-binding domains. Data based on these two independent methods showed the same positive relationship between the total centromere size and genome size. Our results demonstrate that the genome size is a strong predictor (R-squared = 0.964) of the total centromere size universally across Eukaryotes. We also show that this relationship is independent of phylogenetic relatedness and centromere type (monocentric, metapolycentric, and holocentric), implying a common mechanism maintaining stable total centromere size in Eukaryotes.
Keywords: Plants; Evolution, Molecular; molekulární evoluce; Genome Size; houby; Animals; délka genomu; Centromere; centromera; Fungi; rostliny; zvířata